IMPLEMENTASI FITUR D-ID AI AVATARS CANVA SEBAGAI MEDIA PEMBELAJARAN OLAHRAGA - Butsiarah Butsiarah; Bahrul Alim; Andi Saiful Alimsyah; Ahmad Yani; Fatoni Fatoni (LPPM Institut Pendidikan Nusantara Global, 2025)
Innovative learning media has an important role in improving the quality of education, especially in the fields of physical education, health, and recreation. This service is related to the implementation of the D-ID AI Avatars feature in Canva as a sports learning media. By using AI technology, teaching becomes more interesting and interactive. This service aims to explore the effectiveness of using this media in improving students' understanding of sports learning materials. The results obtained from this service show that the use of this media is very effective in helping to understand sports concepts, showing that the use of this media has succeeded in improving understanding visually and interactively and supporting a more dynamic learning process.